Composite membrane, self-adhesive polymer modified asphalt waterproof coiled material and preparation method of self-adhesive polymer modified asphalt waterproof coiled material
Through composite membrane structure and impregnation liquid technology, the problem of deformation and water dissipation of self-adhesive polymer modified asphalt coils during construction is solved, high-quality waterproofing effect and tear resistance are achieved, and the requirements of building waterproofing specifications are met. .
Patent Information
- Application Number
- CN202411358081.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The existing self-adhesive polymer modified asphalt coils are prone to deformation, creases and water bleeding channels during construction, resulting in poor waterproofing effect, insufficient tear resistance and dimensional stability, which affects the quality of the waterproof project.
A composite film structure is adopted, including a first film layer, a second film layer and a third film layer. The second film layer is impregnated with a fiber membrane through an impregnation liquid to improve tensile and tear resistance. The third film layer is enhanced as an interface bonding layer. Adhesion, combining hot melt adhesive layer and asphalt adhesive layer to form a multi-layer multi-material design coil.
It realizes the flatness of the self-adhesive asphalt layer and the sealing of the overlapping edges, improves the softness and perseverance of the coil material, enhances the tear resistance of nail rods and dimensional stability, and meets the high-quality needs of waterproofing projects.
Smart Images

Figure CN119305278A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of membrane materials, and in particular to a composite membrane, a self-adhesive polymer modified asphalt waterproofing coiled material and a preparation method thereof. Background Art
[0002] Self-adhesive polymer modified asphalt membrane has the characteristics of self-adhesion. It can be cold-adhesively constructed without the use of open flames. It is convenient to construct, safe and environmentally friendly, and is widely used. The tireless self-adhesive polymer modified asphalt membrane consists of a membrane layer, a self-adhesive polymer asphalt layer, and an isolation membrane. The membrane material is mainly PE film and PET film according to the type of material. In the actual production process, due to the tension of the production line and the winding, the deformation of the membrane material can easily cause wrinkles and unevenness in the self-adhesive polymer asphalt layer of the membrane, resulting in the formation of water channels at the overlapping edges of the membrane construction and uneven surfaces after the membrane is laid. When there is a water channel at the overlapping edge of the membrane, it is very easy to cause water leakage at the overlapping edge or it cannot withstand high water pressure, affecting the quality of the waterproofing project.
[0003] Existing technologies such as patent CN114347624A disclose a hydrophobic mineral waterproofing coiled material and its preparation process, which includes an isolation membrane, a first asphalt coating layer, a base, a second asphalt coating layer and a surface protective layer arranged in sequence from bottom to top; wherein the material of the surface protective layer is a hydrophobic mineral material, which includes 4000 parts by weight of washed schist, 8-10 parts by weight of silane coupling agent and 75-100 parts by weight of hydrogenated mineral oil. The hydrophobic mineral waterproofing coiled material has a waterproof effect, can effectively prevent water vapor from contacting the coiled material, and has strong adhesion, thereby extending the service life of the coiled material.
[0004] For example, patent CN114523744A discloses a kind of SBS coiled material for high-cold areas and its preparation process. The SBS coiled material for high-cold areas includes a first isolation layer, an upper asphalt coating layer, a tire base, a lower asphalt coating layer and a second isolation layer arranged in sequence from top to bottom; the materials of the first isolation layer and the second isolation layer are both PE film; the materials of the upper asphalt coating layer and the lower asphalt coating layer are both coating materials, and the coating materials include 90# asphalt, SBS, silica gel powder, rubber powder, engine oil, PP particles and fillers; the tire base is a filament polyester tire base cloth dipped in prepreg, and the prepreg includes 90# asphalt, APAO and SBS. The SBS coiled material for high-cold areas meets the standard requirements.
[0005] However, the above two patents did not further explore the tear resistance, dimensional stability and other issues of the related products. In view of the problems of the prior art, a composite membrane, a self-adhesive polymer modified asphalt waterproofing membrane and a preparation method with excellent performance are sought. Summary of the invention
[0006] The present invention aims to solve the problems in the prior art and provides a composite membrane, a self-adhesive polymer modified asphalt waterproofing coiled material and a preparation method. The coiled material prepared by the composite membrane has the advantages of a flat self-adhesive asphalt layer, a dense overlapped edge and no water leakage, and has the characteristics of tear resistance, excellent dimensional stability, soft coiled material and good construction compliance. It can meet the needs of maintenance and new roof waterproofing projects.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] The present invention provides a composite film, comprising a first film layer, a second film layer and a third film layer;
[0009] The first film layer comprises a polyolefin film, a polyester film, a modified polyolefin film or a modified polyester film;
[0010] The second membrane layer comprises a fiber membrane impregnated with an impregnation liquid;
[0011] The third film layer comprises a modified polyolefin film or a modified polyester film;
[0012] The impregnation liquid includes asphalt and silica gel.
[0013] Furthermore, the impregnation liquid comprises 30-50 parts of asphalt and 20-50 parts of silica gel by weight.
[0014] Preferably, the impregnation liquid comprises 30-35 parts of asphalt and 35-40 parts of silica gel by weight.
[0015] Further preferably, the impregnation liquid comprises 32 parts of asphalt and 36 parts of silica gel by weight.
[0016] Furthermore, the polyolefin film includes a PE film, a PP film, a TPO film or a POE film; the polyester film includes a PET film; the modified polyolefin film includes a polyester alloy film (purchased from Henan Jinyinda Materials Co., Ltd., brand E180Y); the modified polyolefin film includes a modified PE film (purchased from Jiangsu Youpers Materials Technology Co., Ltd.).
[0017] Preferably, the silica gel is liquid silica gel, and the asphalt is 200# asphalt.
[0018] Furthermore, the preparation method of the impregnation liquid comprises the following steps: mixing silica gel and asphalt.
[0019] In some specific embodiments, the method for preparing the impregnation liquid comprises the following steps: adding silica gel and asphalt into a stirring tank, starting stirring, and controlling the temperature of the stirring tank to be below 30°C.
[0020] Furthermore, the impregnation liquid also includes one or more of a curing agent, a filler and an auxiliary agent.
[0021] Furthermore, the auxiliary agent includes a first auxiliary agent and / or a second auxiliary agent, the first auxiliary agent includes a plasticizer, and the second auxiliary agent includes a silane coupling agent; the filler includes a first filler and / or a second filler, the first filler includes one or more of calcium carbonate, talc, barium sulfate, wollastonite and mica powder, and the second filler includes a pigment filler.
[0022] Furthermore, the plasticizer is an ester plasticizer, including phthalates and / or fatty acid dibasic esters, specifically one or more of diisooctyl phthalate, diisodecyl phthalate and di(2-ethyl)hexyl sebacate; the silane coupling agent includes one or more of vinyl silane, aminosilane and methyl methacryl silane; the color filler includes one or more of carbon black, black iron oxide, graphite, white carbon black and iron brown.
[0023] Preferably, the impregnation liquid further comprises asphalt, silica gel, a curing agent and a silane coupling agent.
[0024] Further preferably, the impregnation liquid comprises 30-50 parts of asphalt, 20-50 parts of silica gel, 2-5 parts of curing agent and 0.1-1 part of silane coupling agent in parts by weight;
[0025] More preferably, the impregnation liquid comprises, by weight, 30-35 parts of asphalt, 35-40 parts of silica gel, 3.5-4.0 parts of curing agent and 0.4-0.7 parts of silane coupling agent;
[0026] More preferably, the impregnation liquid includes 32 parts of asphalt, 36 parts of silica gel, 3.6 parts of curing agent and 0.5 parts of silane coupling agent.
[0027] Furthermore, the preparation method of the impregnation liquid comprises the following steps: mixing and stirring silica gel, asphalt and silane coupling agent, adding curing agent and stirring to obtain the impregnation liquid.
[0028] In some specific embodiments, the method for preparing the impregnation liquid includes the following steps: adding silica gel, asphalt, and silane coupling agent into a stirring tank, starting stirring, adding a curing agent into the stirring tank, stirring, and controlling the temperature of the stirring tank to be below 30°C.
[0029] Preferably, the impregnation liquid also includes asphalt, silica gel, a curing agent, a filler and an additive.
[0030] Further preferably, the impregnation liquid comprises, by weight, 30-50 parts of asphalt, 20-50 parts of silica gel, 2-5 parts of curing agent, 10-30 parts of first filler, 1-5 parts of second filler, 1-10 parts of first auxiliary agent and 0.1-1 parts of second auxiliary agent;
[0031] More preferably, the impregnation liquid comprises, by weight, 30-35 parts of asphalt, 35-40 parts of silica gel, 3.5-4.0 parts of curing agent, 15-20 parts of first filler, 1-3 parts of second filler, 5-7 parts of first auxiliary agent and 0.4-0.7 parts of second auxiliary agent;
[0032] More preferably, the impregnation liquid includes, by weight, 32 parts of asphalt, 36 parts of silica gel, 3.6 parts of curing agent, 18 parts of first filler, 2 parts of second filler, 6 parts of first auxiliary agent and 0.5 parts of second auxiliary agent.
[0033] Further preferably, the method for preparing the impregnation solution comprises the following steps:
[0034] S1: Mix and stir silica gel, asphalt and the first additive;
[0035] S2: adding the first filler;
[0036] S3: adding the second filler;
[0037] S4: Add curing agent and the second auxiliary agent, stir and obtain.
[0038] In some specific embodiments, the method for preparing the impregnation solution comprises the following steps:
[0039] S1: Add liquid silica gel, asphalt and the first additive into a mixing tank and start stirring;
[0040] S2: adding the first filler into the mixing tank;
[0041] S3: adding the second filler into the mixing tank;
[0042] S4: Add the curing agent and the second auxiliary agent into the stirring tank, and control the temperature of the stirring tank below 30°C.
[0043] Furthermore, the fiber membrane includes a single-component fiber membrane or a bi-component fiber membrane, the single-component fiber membrane includes a polyester fiber membrane or a polyolefin fiber membrane; the bi-component fiber membrane includes a polyolefin-polyester membrane, a polyester-polyester membrane, a polyester-nylon membrane or a polyolefin-polyolefin membrane.
[0044] Furthermore, the polyester fiber film is a polyethylene terephthalate fiber film, the polyolefin fiber film is a polypropylene fiber film or a polyethylene fiber film, the polyolefin-polyester film is a polypropylene-polyethylene terephthalate fiber film, the polyester-polyester film is a polyethylene terephthalate-polyethylene terephthalate fiber film, the polyester-nylon film is a polyethylene terephthalate-polyamide fiber film, and the polyolefin-polyolefin film is a polypropylene-polyethylene fiber film.
[0045] Furthermore, the surface of the third film layer is subjected to corona treatment.
[0046] Furthermore, a first adhesive layer is arranged between the first film layer and the second film layer, and a second adhesive layer is arranged between the second film layer and the third film layer; the first adhesive layer and the second adhesive layer both include hot melt adhesive, acrylic adhesive, polyurethane adhesive or asphalt adhesive.
[0047] Furthermore, the thickness of the first film layer is 5-60 μm, the thickness of the second film layer is 0.1-0.8 mm, and the thickness of the third film layer is 5-110 μm; the thickness of the first adhesive layer and the second adhesive layer are both 3-500 μm.
[0048] Preferably, the thickness of the first film layer is 10-25 μm, the thickness of the second film layer is 0.2-0.4 mm, and the thickness of the third film layer is 40-60 μm; the thickness of the first adhesive layer and the second adhesive layer are both 100-200 μm.
[0049] Further preferably, the thickness of the first film layer is 15 μm, the thickness of the second film layer is 0.3 mm, and the thickness of the third film layer is 50 μm; the thickness of the first adhesive layer and the second adhesive layer are both 150 μm.
[0050] Furthermore, the present invention also provides a method for preparing the above-mentioned composite film, comprising the following steps:
[0051] (1) Unrolling and unwinding the first film layer;
[0052] (2) unfolding and unwinding the fiber membrane;
[0053] (3) Immersing the fiber membrane in the impregnation liquid and scraping it flat;
[0054] (4) curing the fiber membrane to obtain a second membrane layer;
[0055] (5) bonding the first film layer and the second film layer;
[0056] (6) bonding the third film layer to the second film layer;
[0057] (7) Correct the deviation and rewind the roll.
[0058] It is worth noting that step (5) refers to bonding one side of the first film layer to one side of the second film layer, and step (6) refers to bonding one side of the third film layer to the other side of the second film layer.
[0059] In some specific embodiments, the method for preparing the composite membrane comprises the following steps:
[0060] (1) Unrolling and unwinding the first film layer;
[0061] (2) unfolding and unwinding the fiber membrane;
[0062] (3) Immersing the fiber membrane in the impregnation liquid, and scraping both sides of the fiber membrane flat with a scraper;
[0063] (4) transporting the fiber film to an oven at 140-180° C. for curing to obtain a second film layer;
[0064] (5) bonding the first film layer and the second film layer;
[0065] (6) bonding the third film layer to the second film layer;
[0066] (7) Correct the deviation and rewind the roll.
[0067] Furthermore, the present invention also provides a coiled material, comprising the composite film mentioned above or the composite film prepared by the above preparation method.
[0068] Furthermore, the coiled material also includes an isolation layer and / or a self-adhesive asphalt layer.
[0069] Furthermore, the self-adhesive asphalt layer is a self-adhesive polymer asphalt layer that meets the GB 23441-2009 standard; preferably, the self-adhesive asphalt layer is one that meets the standard Type I or Type II.
[0070] Preferably, the self-adhesive polymer asphalt layer is composed of 50-70 parts of asphalt, 10-18 parts of polymer modifier, 10-20 parts of filler, and 0.2-2 parts of tackifying resin. The asphalt is 70# asphalt, the polymer modifier is SBS and SIS, the weight ratio of SBS to SIS is 1:0.2-0.7, and the filler is one or more of stone powder, calcium carbonate and talcum powder. Further preferably, the polymer modifier is SBS and SIS, the weight ratio of SBS to SIS is 1:0.5, and the filler is calcium carbonate.
[0071] Furthermore, the isolation layer includes a PE film, a PP film, a PET film, a PA / PP co-extruded film or a PA / PE co-extruded film.
[0072] Furthermore, the present invention also provides a method for preparing the above-mentioned coiled material, comprising the following steps:
[0073] ① Unwind and correct the isolation layer;
[0074] ②Apply the self-adhesive asphalt layer on the isolation layer;
[0076] ③ Cover the composite membrane on the self-adhesive asphalt layer;
[0077] ④Correct deviation and rewind.
[0078] In some specific embodiments, the method for preparing the coiled material comprises the following steps:
[0079] ① Unwind and correct the isolation layer;
[0080] ② Apply the self-adhesive asphalt layer on the isolation layer, and control the coating temperature at 140-160℃;
[0081] ③ Cover the composite film on the self-adhesive asphalt layer, and control the film covering temperature at 40-60℃;
[0082] ④Correct deviation and rewind.
[0083] The technical effects achieved by the present invention are:
[0084] 1. The present invention provides a composite membrane, which adopts a multi-layer and multi-material composite design and is composed of a first membrane layer, a first adhesive layer, a second membrane layer, a second adhesive layer, and a third membrane layer. Among them, the second membrane layer adopts an impregnated fiber membrane as a skeleton support layer to give the membrane material excellent tensile and tear resistance and high elongation properties. The first membrane layer is a surface layer, which can be designed with color, pattern requirements, weather resistance and other functional requirements. The third membrane layer is an interface bonding layer, which improves the bonding between the functional composite membrane layer and the lower self-adhesive polymer asphalt layer.
[0085] 2. The composite membrane of the present invention uses an impregnation liquid, which can be evenly attached to the fiber surface, increasing the compatibility and adhesion between the fiber membrane and the upper and lower adhesive layers. The introduction of cross-linkable and curable liquid silicone into the fiber impregnation liquid allows the impregnation liquid to be cured into a film at high temperature. On the one hand, the fiber impregnation liquid has excellent high temperature resistance after film formation. On the other hand, the fiber membrane has excellent dimensional stability, tensile strength and deformation resistance after curing after impregnation with the impregnation liquid. The silicone is soft after curing, so that the prepared functional composite membrane layer is also soft, and the corresponding self-adhesive coil is also soft and docile, and has excellent mechanical properties.
[0086] 3. The present invention provides a coiled material, which consists of a three-layer structure. After winding, the self-adhesive asphalt layer has no wrinkles, the upper surface of the coiled material is flat and wrinkle-free, and the coiled material is soft and docile during construction. On the one hand, the full adhesion rate of the large surface of the self-adhesive asphalt layer can be improved, and on the other hand, the overlapping edge of the coiled material has excellent sealing performance, and the overlapping edge is impermeable and water-proof, which effectively improves the quality of waterproof engineering. The functional composite membrane layer uses impregnated fiber as the main layer, which can improve the self-adhesive coiled material's ability to resist nail rod tearing. The coiled material of the present invention meets the requirements of GB 55030-2022 "General Specification for Waterproofing of Buildings and Municipal Engineering", that is, the requirement for the impermeability of the overlapping seams of self-adhesive polymer modified asphalt waterproofing coiled materials is 0.2MPa when there is no treatment, and it is impermeable for 30 minutes. BRIEF DESCRIPTION OF THE DRAWINGS
[0087] Figure 1 is a schematic diagram of the structure of the composite membrane;
[0088] Figure 2 It is a schematic diagram of the structure of the coil;
[0089] Among them, 1-first film layer, 2-first adhesive layer, 3-second film layer, 4-second adhesive layer, 5-third film layer, 6-composite film, 7-self-adhesive asphalt layer, 8-isolating layer. DETAILED DESCRIPTION
[0090] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0091] Before further describing the specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the examples of the present invention are for describing specific embodiments rather than for limiting the scope of protection of the present invention.
[0092] When the embodiment gives a numerical range, it should be understood that, unless otherwise specified in the present invention, the two endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the present invention belongs.
[0093] It is worth noting that the modified polyolefin film used in the present invention is a polyester alloy film (purchased from Henan Jinyinda Materials Co., Ltd., with the brand name E180Y); the modified polyester film is a modified PE film (purchased from Jiangsu Youpers Materials Technology Co., Ltd.); the asphalt is 200# asphalt; the silica gel is liquid silica gel, and the silica gel and curing agent are both purchased from Shenzhen Hongye Technology Co., Ltd., with the brand name E630; the self-adhesive asphalt layer is a self-adhesive polymer asphalt layer that meets the GB 23441-2009 standard; specifically, it meets the standard Type I (the self-adhesive polymer asphalt layer is composed of 60 parts of asphalt, 15 parts of polymer modifier, 15 parts of filler, and 1 part of tackifying resin. The asphalt is 70# asphalt, the polymer modifiers are SBS and SIS, the weight ratio of SBS to SIS is 1:0.5, and the filler is calcium carbonate).
[0094] The second film layer of polyethylene terephthalate fiber film and polypropylene fiber film were purchased from Wenzhou Chaocheng Nonwoven Technology Co., Ltd.; polypropylene-polyethylene terephthalate fiber film and polyethylene terephthalate-polyamide fiber film were purchased from Freudenberg High Performance Materials Group; polyethylene terephthalate-polyethylene terephthalate fiber film was purchased from Shandong Taipeng Environmental Protection Materials Co., Ltd.;
[0095] The remaining raw materials are all common commercially available products, so their sources are not specifically limited.
[0096] The structural schematic diagram of the composite membrane in the present invention is as follows Figure 1 As shown, a first film layer 1, a second film layer 3 and a third film layer 5 are sequentially arranged from top to bottom, wherein a first adhesive layer 2 is arranged between the first film layer 1 and the second film layer 3, and a second adhesive layer 4 is arranged between the second film layer 3 and the third film layer 5; the structural schematic diagram of the coil is shown in Figure 2 As shown, a composite membrane 6, a self-adhesive asphalt layer 7 and an isolation layer 8 are arranged in sequence from top to bottom.
[0097] Embodiment 1-9:
[0098] The composition and thickness of the composite films of Examples 1-9 are shown in Table 1:
[0099] Table 1 Composite film composition and thickness
[0100]
[0101]
[0102] The impregnation liquid used in the second film layer of each embodiment in Table 1 is shown in Table 2:
[0103] Table 2 Composition and content of the impregnation solution (unit: weight parts)
[0104]
[0105]
[0106] The preparation method of the composite film in the embodiment is specifically the following steps:
[0107] (1) Unrolling and unwinding the first film layer;
[0108] (2) unfolding and unwinding the fiber membrane;
[0109] (3) Immersing the fiber membrane in the impregnation liquid and scraping it flat;
[0110] (4) curing the fiber membrane to obtain a second membrane layer;
[0111] (5) bonding the first film layer and the second film layer;
[0112] (6) bonding the third film layer to the second film layer;
[0113] (7) Correct the deviation and rewind the roll.
[0114] The preparation method of the impregnation liquid in Examples 1-3 is specifically the following steps: adding liquid silica gel and asphalt into a stirring tank, starting stirring, and controlling the temperature of the stirring tank to be below 30°C.
[0115] The preparation method of the impregnation liquid in Examples 4-6 is specifically the following steps: adding liquid silica gel and asphalt into a stirring tank and starting stirring; adding a curing agent and a second auxiliary agent into the stirring tank and controlling the temperature of the stirring tank to be below 30°C.
[0116] The preparation method of the impregnation solution in Examples 7-9 is specifically the following steps:
[0117] S1: Add liquid silica gel, asphalt and the first additive into a mixing tank and start stirring;
[0118] S2: adding the first filler into the mixing tank;
[0119] S3: adding the second filler into the mixing tank;
[0120] S4: Add the curing agent and the second auxiliary agent into the stirring tank, and control the temperature of the stirring tank below 30°C.
[0121] Application Examples 1-9:
[0122] The composite films prepared in Examples 1-9 were respectively used to prepare the coils, as shown in the following table:
[0123] Table 3 Coil composition and thickness (unit: μm)
[0124]
[0125]
[0126] In each embodiment, the thickness of the isolation layer is 40 μm, and the thickness of the self-adhesive asphalt layer is 1.5 mm.
[0127] The preparation method of the coiled material in the application example is specifically the following steps:
[0128] ① Unwind and correct the isolation layer;
[0129] ② Apply the self-adhesive asphalt layer on the isolation layer, and control the coating temperature at 150℃;
[0130] ③ Cover the composite film on the self-adhesive asphalt layer, and control the covering temperature at 50℃;
[0131] ④Correct deviation and rewind.
[0132] Comparative Example 1
[0133] The only difference from Example 1 is that the first film layer and the second film layer are replaced by a third film layer of equal thickness.
[0134] That is, the composite film specifically contains a 65.3 μm third film layer, a 150 μm first adhesive layer and a 150 μm second adhesive layer.
[0135] The preparation method is the same as Example 1.
[0136] Comparative Example 2
[0137] The only difference from Example 1 is that the second film layer and the third film layer are replaced by the first film layer of the same thickness.
[0138] That is, the composite film specifically contains a first film layer of 65.3 μm, a first adhesive layer of 150 μm and a second adhesive layer of 150 μm.
[0139] The preparation method is the same as Example 1.
[0141] Comparative Example 3
[0142] The only difference from Example 1 is that the first film layer and the third film layer are replaced by a second film layer of equal thickness.
[0143] That is, the composite film specifically contains a 65.3 μm second film layer, a 150 μm first adhesive layer and a 150 μm second adhesive layer.
[0144] The preparation method is the same as Example 1.
[0145] Comparative Example 4
[0146] The only difference from Example 7 is that the first film layer and the second film layer are replaced by a third film layer of equal thickness.
[0147] That is, the composite film specifically contains a 65.3 μm third film layer, a 150 μm first adhesive layer and a 150 μm second adhesive layer.
[0148] The preparation method is the same as Example 7.
[0149] Comparative Example 5
[0150] The only difference from Example 7 is that the second film layer and the third film layer are replaced by the first film layer of the same thickness.
[0151] That is, the composite film specifically contains a first film layer of 65.3 μm, a first adhesive layer of 150 μm and a second adhesive layer of 150 μm.
[0152] The preparation method is the same as Example 7.
[0153] Comparative Example 6
[0154] The only difference from Example 7 is that the first film layer and the third film layer are replaced by a second film layer of equal thickness.
[0155] That is, the composite film specifically contains a 65.3 μm second film layer, a 150 μm first adhesive layer and a 150 μm second adhesive layer.
[0156] The preparation method is the same as Example 7.
[0157] Application Comparative Examples 1-6:
[0158] The composite films of Comparative Examples 1-6 were respectively used to prepare coiled materials, and the thickness of the isolation layer, the thickness of the self-adhesive asphalt layer and the specific preparation method were the same as those in Application Example 1.
[0159] Application Comparative Example 7
[0160] The only difference from Application Example 1 is that the composite film is replaced by a PE film during the preparation of the coil.
[0161] Application Comparative Example 8
[0162] The only difference from Application Example 7 is that the composite film is replaced by a PE film during coil preparation.
[0163] The waterproof membranes prepared in the application examples and the application comparison examples were tested for performance, as follows.
[0164] 1. Joint impermeability: Refer to the test method of T / CWA 302-2023 Building Waterproof Material Engineering Requirements;
[0165] 2. Appearance of the roll and the self-adhesive asphalt layer: Unroll the roll and lay it flat to observe the flatness of the upper surface of the roll. Remove the isolation film on the lower surface of the roll and observe the flatness of the self-adhesive asphalt layer;
[0166] 3. Nail rod tearing strength: refer to GB23441-2009 test;
[0167] 4. Dimensional stability: Refer to GB23441-2009 test.
[0168] The results are summarized in the following table:
[0169] Table 4 Test results of embodiments and comparative examples
[0170]
[0171]
[0172] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A composite film, characterized in that: comprising a first film layer, a second film layer and a third film layer; The first film layer comprises a polyolefin film, a polyester film, a modified polyolefin film or a modified polyester film; The second membrane layer comprises a fiber membrane impregnated with an impregnation liquid; The third film layer comprises a modified polyolefin film or a modified polyester film; The impregnation liquid includes asphalt and silica gel.
2. The composite membrane according to claim 1, characterized in that: In parts by weight, the impregnation liquid comprises 30-50 parts of asphalt and 20-50 parts of silica gel; preferably, in parts by weight, the impregnation liquid comprises 30-35 parts of asphalt and 35-40 parts of silica gel; further preferably, in parts by weight, the impregnation liquid comprises 32 parts of asphalt and 36 parts of silica gel.
3. The composite membrane according to claim 1, characterized in that: The polyolefin film includes a PE film, a PP film, a TPO film or a POE film; the polyester film includes a PET film; the modified polyolefin film includes a polyester alloy film; and the modified polyolefin film includes a modified PE film.
4. The composite membrane according to claim 1, characterized in that: The impregnation liquid further comprises one or more of a curing agent, a filler and an auxiliary agent.
5. The composite membrane according to claim 4, characterized in that: The auxiliary agent includes a first auxiliary agent and / or a second auxiliary agent, the first auxiliary agent includes a plasticizer, and the second auxiliary agent includes a silane coupling agent; the filler includes a first filler and / or a second filler, the first filler includes one or more of calcium carbonate, talcum powder, barium sulfate, wollastonite and mica powder, and the second filler includes a pigment filler.
6. The composite membrane according to claim 5, characterized in that: The plasticizer includes phthalates and / or fatty acid dibasic esters, the silane coupling agent includes one or more of vinyl silane, amino silane and methyl acryloyl silane; the pigment filler includes one or more of carbon black, black iron oxide, graphite, white carbon black and iron brown.
7. The composite membrane according to claim 4, characterized in that: In parts by weight, the impregnation liquid comprises 30-50 parts of asphalt, 20-50 parts of silica gel, 2-5 parts of curing agent and 0.1-1 parts of silane coupling agent; preferably, in parts by weight, the impregnation liquid comprises 30-35 parts of asphalt, 35-40 parts of silica gel, 3.5-4.0 parts of curing agent and 0.4-0.7 parts of silane coupling agent; further preferably, the impregnation liquid comprises 32 parts of asphalt, 36 parts of silica gel, 3.6 parts of curing agent and 0.5 parts of silane coupling agent.
8. The composite membrane according to claim 4, characterized in that: In parts by weight, the impregnating liquid comprises 30-50 parts of asphalt, 20-50 parts of silica gel, 2-5 parts of curing agent, 10-30 parts of first filler, 1-5 parts of second filler, 1-10 parts of first auxiliary agent and 0.1-1 parts of second auxiliary agent; preferably, in parts by weight, the impregnating liquid comprises 30-35 parts of asphalt, 35-40 parts of silica gel, 3.5-4.0 parts of curing agent, 15-20 parts of first filler, 1-3 parts of second filler, 5-7 parts of first auxiliary agent and 0.4-0.7 parts of second auxiliary agent; further preferably, in parts by weight, the impregnating liquid comprises 32 parts of asphalt, 36 parts of silica gel, 3.6 parts of curing agent, 18 parts of first filler, 2 parts of second filler, 6 parts of first auxiliary agent and 0.5 parts of second auxiliary agent.
9. The composite membrane according to claim 1, characterized in that: The fiber membrane includes a single-component fiber membrane or a two-component fiber membrane. The single-component fiber membrane includes a polyester fiber membrane or a polyolefin fiber membrane; the two-component fiber membrane includes a polyolefin-polyester membrane, a polyester-polyester membrane, a polyester-nylon membrane or a polyolefin-polyolefin membrane.
10. The composite membrane according to claim 1, characterized in that: The surface of the third film layer is subjected to corona treatment.
11. The composite membrane according to claim 1, characterized in that: A first adhesive layer is arranged between the first film layer and the second film layer, and a second adhesive layer is arranged between the second film layer and the third film layer; the first adhesive layer and the second adhesive layer both include hot melt adhesive, acrylic adhesive, polyurethane adhesive or asphalt adhesive.
12. The composite membrane according to claim 11, characterized in that: The thickness of the first film layer is 5-60μm, the thickness of the second film layer is 0.1-0.8mm, and the thickness of the third film layer is 5-110μm; the thickness of the first adhesive layer and the second adhesive layer are both 3-500μm; preferably, the thickness of the first film layer is 10-25μm, the thickness of the second film layer is 0.2-0.4mm, and the thickness of the third film layer is 40-60μm; the thickness of the first adhesive layer and the second adhesive layer are both 100-200μm; further preferably, the thickness of the first film layer is 15μm, the thickness of the second film layer is 0.3mm, and the thickness of the third film layer is 50μm; the thickness of the first adhesive layer and the second adhesive layer are both 150μm.
13. The method for preparing a composite membrane according to any one of claims 1 to 12, characterized in that: The following steps are involved: (1) Unrolling and unwinding the first film layer; (2) unfolding and unwinding the fiber membrane; (3) Immersing the fiber membrane in the impregnation liquid and scraping it flat; (4) curing the fiber membrane to obtain a second membrane layer; (5) bonding the first film layer and the second film layer; (6) bonding the third film layer to the second film layer; (7) Correct the deviation and rewind the roll.
14. A coiled material, characterized in that: It includes the composite film according to any one of claims 1 to 12 or the composite film prepared by the preparation method according to claim 13.
15. The coiled material according to claim 14, characterized in that: Also included are a barrier layer and / or a self-adhesive bitumen layer.
16. The coiled material according to claim 15, characterized in that: The isolation layer includes a PE film, a PP film, a PET film, a PA / PP co-extruded film or a PA / PE co-extruded film.
17. The method for preparing a coiled material according to any one of claims 14 to 16, characterized in that: The following steps are involved: ① Unwind and correct the isolation layer; ②Apply the self-adhesive asphalt layer on the isolation layer; ③ Cover the composite membrane on the self-adhesive asphalt layer; ④Correct deviation and rewind.
Citation Information
Patent Citations
Crack pressing tape for cracks of asphalt road surface and preparation method of crack pressing tape
CN102535304A
Modified asphalt waterproof roll as well as preparation method and construction process thereof
CN107128052A
Macromolecular composite membrane modified bituminous waterproof roll
CN107627691A
A roofing membrane with protective film
EP4272957A1
White roofing
JP3194556U